PELATIHAN PENULISAN LAGU ANAK UNTUK GURU-GURU TKSEBAGAI MEDIA MITIGASI BENCANA DI YOGYAKARTA - dan Esti Swatika Sari, Heni Kusumawati (Universitas Negeri Yogyakarta, 2012)
The purpose of this training is to practice of the Kindergarden's Teacherswrite children's song as a media of mitigative dissasters. Song is not only asa tool to entertain but alos to teach vocabularly, as well as, to therapy of traumaticat the childrens.This activity involve 35 teachers of Kinderganrden in Cangkringan. Thisactivity has been done in three minnilesons, dated on Juny 25, July first, andJuli Nine. Method of this program is discussion, brainstorming, and demonstration.The result of this program is producing 30 songs has been arranged bythe participants. A theme if these songs is an environment. The participants hasparticipated enthusiasthicly. They have a new knowledge in creating a song andproposes a same program could bee done in next time.